APPROACH TO THE IMPROVEMENT OF THE CONTROL SYSTEM OF THE ELECTRIC POWER PLANT OF THE AIRCRAFT - BOIKO, Sergey; HEBDA, Alona; STUSHCHANSKY, Yurii; GOLOVANOV, Serhiy; RUZHUK, Myhailo (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper proposes an approach to improving the adaptive system of aircraft with an electric propulsion system. Modern aircraft are inextricably linked with electronics that ensure the functioning of the entire air transport system. Modern aircraft avionics is a complex of hardware and software that is part of the automatic control system of the aircraft and functionally combines the glider with the drive of the executive body. One of the main functions of modern avionics is the automation of aircraft control processes, which aims to ensure the proper execution of a safe flight with the smallest number of crew members. this fact encourages the continuous improvement of the existing on-board avionics complexes of aircraft. Among other things, the adaptive control system should determine the dynamic characteristics of the controlled aircraft during the flight, the assessment of the state of the functional systems of the aircraft and the formation of control signals. An approach to the construction of an aircraft control system is proposed, which involves a double determination of the characteristics of the object under study. The structure of the control system of an aircraft with an electric power plant is proposed. Its construction was influenced by the operating features of the aircraft’s electric power plant, the approach to the dual determination of the aircraft’s characteristics, and the principle of dual control of the aircraft’s flight parameters. The paper proposes an approach to improving the adaptive system of aircraft with an electric propulsion system. There are the following factors: 1) height, accuracy and reliability of sensors of all parameters, regardless of operating conditions; 2) a simple and at the same time reliable and functional interface; 3) timely detection of deviations in the operation of aircraft systems during its operation and transmission of relevant information to the crew and the control system; 4) operational determination of the dynamic characteristics of the aircraft during flight and adaptive optimization of controlled signals taking into account the purpose of control and the specified optimization criteria.